Characterizing tobacco control mass media campaigns in England - Langley, Tessa; Lewis, Sarah; McNeill, Ann; Gilmore, Anna; Szatkowski, Lisa; West, Robert; Sims, Michelle (Wiley, 2013)
Aims To characterize publically funded tobacco control campaigns in England between 2004 and 2010 and to explore if they were in line with recommendations from the literature in terms of their content and intensity. International evidence suggests that campaigns which warn of the negative consequences of smoking and feature testimonials from real-life smokers are most effective, and that four exposures per head per month are required to reduce smoking prevalence. Design Characterization of tobacco control advertisements using a theoretically based framework designed to describe advertisement themes, informational and emotional content and style. Study of the intensity of advertising and exposure to different types of advertisement using data on population-level exposure to advertisements shown during the study period. Setting England. Measurements Television Ratings (TVRs), a standard measure of advertising exposure, were used to calculate exposure to each different campaign type. Findings A total of 89% of advertising was for smoking cessation; half of this advertising warned of the negative consequences of smoking, while half contained how-to-quit messages. Acted scenes featured in 72% of advertising, while only 17% featured real-life testimonials. Only 39% of months had at least four exposures to tobacco control campaigns per head. Conclusions A theory-driven approach enabled a systematic characterization of tobacco control advertisements in England. Between 2004 and 2010 only a small proportion of tobacco control advertisements utilized the most effective strategies—negative health effects messages and testimonials from real-life smokers. The intensity of campaigns was lower than international recommendations.